Stakeholder-engaged research: strategies for the prevention and control of overweight and obesity in Kenya - Mary Njeri Wanjau; Lucy W. Kivuti-Bitok; Leopold N. Aminde; J. Lennert Veerman (BMC, 2021)
Abstract Background This study was done as part of a larger study that aims to identify the most impactful and cost-effective strategies for the prevention and control of overweight and obesity in Kenya. Our objective was to involve stakeholders in the identification of the strategies that would be included in our larger study. The results from the stakeholder engagement are analyzed and reported in this paper. Design This was a qualitative study. A one-day stakeholder workshop that followed a deliberative dialogue process was conducted. Participants A sample of stakeholders who participate in the national level policymaking process for health in Kenya. Outcome measure Strategies for the prevention and control of overweight and obesity in Kenya. Results Out of the twenty-three stakeholders who confirmed attendance, fifteen participants attended the one-day workshop. The stakeholders identified a total of 24 strategies for the prevention and control of overweight and obesity in Kenya. From the ranking process carried out the top six strategies identified were: a research-based strategy for the identification of the nutritional value of indigenous foods, implementation of health promotion strategies that focus on the creation of healthy environments, physical activity behavior such as gym attendance, jogging, walking, and running at the individual level, implementation of school curricula on nutrition and health promotion, integration of physical education into the new Competency-Based Education policy, and policies that increase use of public transport. Conclusion The stakeholders identified and ranked strategies for the prevention and control of overweight and obesity in Kenya. This informs future overweight and obesity prevention research and policy in Kenya and similar settings.